Reconstruction The Concept of Islamic Education in the Hadith: Integration of Morals, Knowledge, and Human Nature - Aas Siti Sholichah; Muhamad Wijaksono; Endad Musaddad (Journal of Educational Management Research, 2025)
Education is a fundamental aspect of human life that shapes a person's character, potential, and path. However, in many modern education systems, moral development is often neglected in favor of academic achievement. This study aims to integrate the intellectual, moral, and spiritual dimensions in Islamic education, highlighting the teachings of the Prophet Muhammad (PBUH) on education that prioritizes the development of noble character. The method used is a qualitative, literature-based research, focusing on the Prophet's Hadith related to education. The results show that education in Islam focuses not only on knowledge, but also on the formation of strong moral and spiritual values. This study suggests that modern education systems, especially in Muslim-majority countries, need to adopt a holistic approach that encompasses cognitive, moral, and spiritual learning. The contribution of this study lies in offering a more comprehensive and relevant educational model to the challenges of the times, as well as providing a theoretical and practical foundation for holistic Islamic values-based education.